Analysis of Factors that Influence the Motivation of Generation Z Nurses in RS Islam Siti Rahmah Padang - Alfanira; Rahmat Syukri (Professional Evidence-based Research and Advances in Wellness and Treatment, 2026)
The transformation of the world of work challenges hospitals in managing a multigenerational workforce, particularly Generation Z nurses, who have high expectations for career development, work–life balance, and recognition. Unmet expectations may reduce work motivation and affect healthcare quality. This study examines factors influencing the work motivation of Generation Z nurses using a quantitative descriptive approach at RS Islam Siti Rahmah Padang, involving 50 nurses selected through purposive sampling. Data were collected through questionnaires and analyzed using univariate analysis and multiple linear regression. The results showed that compensation and career development were perceived as the most influential factors (70%) and had a significant effect on work motivation (p = 0.000; p = 0.002). In contrast, the work environment and leadership showed no significant effect. These findings emphasize the need to strengthen compensation systems and career development programs to enhance Generation Z nurses’ motivation and healthcare service quality.